Familial cramp due to potassium-aggravated myotonia. Issue 4 (1st October 1998) - Orrell, Richard W; Jurkat-Rott, Karin; Lehmann-Horn, Frank; Lane, Russell J M
Abstract : Clinical, electrophysiological, and molecular genetic features were investigated in two patients from a family a with dominantly inherited myotonic disease, characterised by painful cramps, stiffness without weakness, fluctuation of symptoms, and cold sensitivity. A reduction in amplitude of the compound muscle action potential was demonstrated on cooling and administration of potassium, although no clinical exacerbation was seen. A heterozygote mutation Val1589Met was identified in the α-subunit of the skeletal muscle sodium channel gene in both patients, consistent with the diagnosis of potassium-aggravated myotonia. The phenotype in this family is much milder than that previously described in another family with a mutation at this site.